Note on Abel Summability of Double Series. (3rd August 2017) - Yeşilkayagil, Medine; Başar, Feyzi
ABSTRACT: In this paper, we prove that if a double series converges to α, then the power series converges for all x, y ∈(0, 1) and its sum is α, as . But the converse of this is not true, in general. Our main goal is to show that the converse of the idea, above, is true under which condition/conditions.